Food safety: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
Food safety and sanitary and phytosanitary standards (SPS) are increasingly important barriers to ACP countries’ exports of food and agricultural products not only to the EU, but also to other international and regional markets. This Executive Brief explores the developments of food safety and SPS standards in 2012-13. It focuses on the interactions of the different policy measures at national, regional and international levels, and their trade consequences for ACP countries. A series of challenges are also outlined, such as the development of national institutions’ capacity for setting up cost-effective control systems, and the establishment of harmonized regional standards that would facilitate ACP’s export diversification.